1977
DOI: 10.1083/jcb.75.1.237
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical investigations of retinotectal adhesive specificity

Abstract: The preferential adhesion of chick neural retina cells to surfaces of intact optic tecta has been investigated biochemically. The study uses a collection assay in which single cells from either dorsal or ventral halves of neural retina adhere preferentially to ventral or dorsal halves of optic tecta, respectively. The data presented support the following conclusions: (a) The adhesion of ventral retina to dorsal tecta seems to depend on proteins located on ventral retina and on terminal /3-N-acetylgalactosamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(38 citation statements)
references
References 42 publications
1
37
0
Order By: Relevance
“…A dorsal--ventral gradient of GM2 ganglioside molecules (II3NeuAc-GgOse3Cer) in chicken embrvo retina has been postulated but not detected (15 TOP antigenicity was upon incubation at 100°C or by incubation with trypsin ( Table 2). All TOP antigenicity in retina cell homogenates was recovered from the 100,000 X g particulate fraction; soluble antigen was not detected (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…A dorsal--ventral gradient of GM2 ganglioside molecules (II3NeuAc-GgOse3Cer) in chicken embrvo retina has been postulated but not detected (15 TOP antigenicity was upon incubation at 100°C or by incubation with trypsin ( Table 2). All TOP antigenicity in retina cell homogenates was recovered from the 100,000 X g particulate fraction; soluble antigen was not detected (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Other work has shown that dorsal and ventral chicken retinal cell suspensions differ reciprocally in their adhesion to monolayers of ventral and dorsal tectal cells (2). Based on the sensitivity of these adhesive interactions to enzyme treatments, a double-gradient model involving a ganglioside and a ,8-N-acetylgalactosamine-binding protein was postulated (3).…”
Section: Introductionmentioning
confidence: 99%
“…Gangliosides have been associated with regions ofneuronal and glial proliferation (Goldman et al, 1984;Levine et al, 1984) and with the differentiation of neuronal and glial cells in culture (Seifert, 198 1;Hefti et al, 1985). Finally, various investigations of cell-cell as well as cell-substratum adhesion have suggested that gangliosides may modulate contact-mediated cell interactions (Barbera et al, 1973;Barbera, 1975;Marchase, 1977;Blackbum et al, 1986;Cheresh and Klier, 1986;Thompson et al, 1986).…”
mentioning
confidence: 99%